Evaluation of Shrink-Swell Soils of Chandrabhaga Valley in Semi-Arid Regions of Central India for Soil Resource Management - Vilas K. Kharche, Prakash R. Kadu (Journal of the Indian Society of Soil Science, 2017)
The present study was undertaken to evaluate the shrink-swell soils of Chandrabhaga valley of central India for various crops. Fourteen typifying pedons representing various landforms were studied. Most of the soils were very high in clay content (31-75%), calcareous in nature, imperfect to moderately drained and very slow to moderate saturated hydraulic conductivity (SHC) (0.01-27.4 mm h-1). Lower values of SHC in some soils were due to higher exchangeable sodium percentage (ESP>5) and/or low Ca2+/Mg2+ ratio (<1.5). The soils were neutral to strongly alkaline, non-saline with ESP well below 5 except in some irrigated soils. They had variable exchangeable Ca2+/Mg2+ ratio (0.9-3.6). Although the temperature regime of the region was conducive for cropping throughout the year, the length of growing period (LGP) was quite variable resulting in variation in moisture availability from soil to soil. The land suitability evaluation indicated that soils had good potential for crop production because of their better rooting depth, high clay of smectitic nature associated with high cation exchange capacity (CEC) and plant available water capacity with a high base status. However, poor drainage mainly in kharif appears to be the main parameter controlling the crop production in the area. The deep rooted crops like cotton and pigeonpea can be successfully grown in well developed Vertisols with SHC higher than 10 mm h-1 while soybean, sorghum and groundnut can be grown on vertic intergrades with relatively higher SHC and better drainage. The productivity of these soils is primarily governed by important parameters like SHC indicating that the determination of measured parameters in a particular crop-climatic-soil environment would be a prudent approach in the field of land evaluation instead of depending upon inferred parameters. Therefore, SHC, ESP and Ca2+/Mg2+ ratio can be regarded as the major soil quality attributes of Vertisols and associated vertic intergrades as they govern the productivity of these soils.